2021
DOI: 10.3389/fphy.2020.579461
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Numerical Solution of the EMI Model Representing the Extracellular Space (E), Cell Membrane (M) and Intracellular Space (I) of a Collection of Cardiac Cells

Abstract: The EMI model represents excitable cells in a more accurate manner than traditional homogenized models at the price of increased computational complexity. The increased complexity of solving the EMI model stems from a significant increase in the number of computational nodes and from the form of the linear systems that need to be solved. Here, we will show that the latter problem can be solved by careful use of operator splitting of the spatially coupled equations. By using this method, the linear systems can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
1

Relationship

4
3

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 38 publications
0
37
0
Order By: Relevance
“…It is therefore of importance to develop a splitting strategy for the EMI model that leads to sub-problems of the elliptic type. In (14), we showed that such a splitting can indeed be achieved. Here, we will review this convenient way of splitting the EMI model and show how to solve the system numerically using a finite difference method.…”
Section: Introductionmentioning
confidence: 82%
“…It is therefore of importance to develop a splitting strategy for the EMI model that leads to sub-problems of the elliptic type. In (14), we showed that such a splitting can indeed be achieved. Here, we will review this convenient way of splitting the EMI model and show how to solve the system numerically using a finite difference method.…”
Section: Introductionmentioning
confidence: 82%
“…This approach represents the extracellular space (E), the cell membrane (M) and the intracellular space (I), see, e.g., [ 38 40 ]. The EMI model equations are solved using an MFEM [ 41 , 42 ] finite element implementation of the splitting algorithm introduced in [ 43 , 44 ]. Technical specifications of the domain geometry and the EMI model solver are provided in the S1 Text .…”
Section: Methodsmentioning
confidence: 99%
“…Note that, is the current density between neighbouring myocytes, specified by the passive model where G gap (in mS/cm 2 ) is the conductance of the gap junctions and R gap (in kΩcm 2 ) is the corresponding resistance of the gap junctions. The parameters used in the EMI model simulations are specified in Table 3, and the EMI model equations are solved numerically using an MFEM [54, 55] finite element implementation of the operator splitting algorithm introduced in [30, 56].…”
Section: Methodsmentioning
confidence: 99%
“…We represent essential features of the geometry of the PV sleeve by constructing a collection of coupled myocytes that form a cylinder having a diameter of 1.5 cm (similar to the diameter of a human PV [57]). Each myocyte is [30].…”
Section: Pv Sleeve Geometrymentioning
confidence: 99%
See 1 more Smart Citation